Forest Operations, Engineering and Management - Raffaele Spinelli (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. The book gathers 28 quality papers containing new and important knowledge on forest operations, engineering and management. Active forest management is indeed applied through forest engineering, and careful forest tending is conditional to the implementation of sound operational methods, which may guarantee cost-effective management while protecting environmental functionality and worker health. Efficiently managed forest operations offer the highest benefit and the lowest cost, in all fields: financial, social and environmental. While maintaining a cross-disciplinary character, forest engineering represents a special sector of interest within the field of forestry and aims at increasing the overall efficiency of forest operations. Forest engineering often deals with practical issues that have a strong economic impact, and for this reason the industry has always had a strong interest in forest engineering, which explains the close connection between scientists and economic operators. The central role of forest engineering in modern forestry is demonstrated by the many sessions gathered under this general label at the IUFRO 125th Anniversary Congress, which offered a great opportunity for catching up with the latest results of sector research. Over the years, much progress has been done in the field of forest engineering, which has been supported by the dramatic technology advances of the most recent times. The 28 papers contained in this book come from many different countries and cover a large variety of subjects, from pure productivity, to resource availability, operation planning, environmental impacts and operator safety and health. Energy biomass is also represented, as a witness to the growing role of forestry in the quest for renewable energy sources.